Preterm Labor and Birth: A Clinical Review. Issue 6 (November 2020) - Griggs, Kellie M.; Hrelic, Debra A.; Williams, Nina; McEwen-Campbell, Michelle; Cypher, Rebecca
Abstract : Abstract: When caring for women experiencing preterm labor and birth, nurses play a significant role as bedside experts, advocates, patient educators, and key members of the maternity care team. Enhanced expertise on clinical and professional knowledge of preterm labor and birth is crucial in prevention and treatment. As preterm birth rates continue to rise, perinatal nurses as well-informed clinical experts have the opportunity to offer innovative education, holistic assessments, and communication through shared decision-making models. Educating pregnant women about early recognition of preterm labor warning signs and symptoms allows for timely diagnosis, interventions, and treatment. Informed and collaborative nursing practice improves quality of clinical care based on individualized interactions. A clinical review of preterm labor and preterm birth is presented for perinatal nurses. Abstract : An overview of current evidence on risk factors and treatment for preterm labor and birth is presented.